Student Attitudes towards Guided Inquiry Approach Supported by Digital Stories - Merve Berika Kansoy; Ayse Sert-Cibik (Journal of Education in Science, Environment and Health)
The aim of this study is to investigate the effects of guided inquiry activities supported by digital stories in the 6th grade science lesson on students’ attitudes towards inquiry. The method of the study was determined as the embedded design, one of the mixed method research designs. 27 students from a public school located in the countryside participated in the study. In the quantitative dimension of the study, a single group pretest-posttest research design was used. Quantitative data were obtained through the Attitude Scale towards Research-Questioning. The qualitative dimension of the study was designed in accordance with the case study model. Qualitative data were obtained by using semi-structured weekly focus group interviews, teacher diaries and observation form. Quantitative data were analyzed with Mann Whitney U-Test, qualitative data were analyzed with descriptive and content analysis methods. As a result, thanks to the applied method, the attitude scores of the lower and middle group students towards inquiry converged to each other. Interviews with students and researcher diaries also support the results. It was revealed how the learning environment, teacher, student and lecturing affect the attitudes of the students participating in the studies towards inquiry